Simulation and experimental investigation of muffler performance - Mohiuddin, A. K. M.; Rahman, Mohammed Ataur; Gazali, Yazid (Universiti Malaya, 2007)
The purpose of the muffler is to reduce the exhaust noise produced by the engine. The main objective of this study is to simulate and investigate experimentally the muffler of the Alfa Romeo 145 vehicle. The dimensions of the muffler were used to perform the simulation. Experimentations were performed with the same muffler to develop a relationship between the noise and back pressure on muffler design. The performance of a muffler is based on Insertion loss, Transmission loss, and Back pressure. To study the performance of the muffler, simulation was carried out using GAMBIT software with FLUENT. GAMBIT was used to create a mesh surface and to define the boundary conditions of the required object, which was read and analyzed by FLUENT. The experiment on the actual muffler of Alfa Romeo 145 was conducted at different engine speed. Experimental investigation was performed on four parameters: manifold temperature, tail pipe temperature, manifold pressure and sound pressure level (SPL). Curves are drawn and analyzed using the measured parameters.